2017
DOI: 10.1111/phpp.12350
|View full text |Cite
|
Sign up to set email alerts
|

An open‐label clinical trial assessing the efficacy and safety of Bend Skincare Anti‐Aging Formula on minimal erythema dose in skin

Abstract: Summary Background/purpose Sunburn and other health risks associated with excess sun exposure place huge economic burdens on societies, and create discomfort and disease within susceptible individuals. Oral supplements that reduce sunburn may be advantageous. This study evaluated the safety and efficacy of Bend Skincare Anti‐Aging Formula to ameliorate sunburn induced with a solar simulator. Methods Subjects (n = 28) with Fitzpatrick skin phototypes I, II, or III took 4 capsules daily of the supplement providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…Regarding the photoprotective effects of LUT, a randomized, controlled, double-blind clinical trial in people exposed to UVB/A demonstrated that capsules of LUT (10 mg, twice daily) decreased the skin expression of HO-1, MMP-1, and ICAM-1 [191]. Moreover, oral supplementation with omega-6 and omega-3 fatty acids, ZX, LUT, and vitamin D attenuated sunburn risk in patients with Fitzpatrick skin phototypes I, II, or III [192]. Finally, a recent study confirmed the photoprotective and antiphotoaging effects of a nutritional intervention with different antioxidants, including LUT (3 mg/day), in healthy volunteers [193].…”
Section: Human Studiesmentioning
confidence: 99%
“…Regarding the photoprotective effects of LUT, a randomized, controlled, double-blind clinical trial in people exposed to UVB/A demonstrated that capsules of LUT (10 mg, twice daily) decreased the skin expression of HO-1, MMP-1, and ICAM-1 [191]. Moreover, oral supplementation with omega-6 and omega-3 fatty acids, ZX, LUT, and vitamin D attenuated sunburn risk in patients with Fitzpatrick skin phototypes I, II, or III [192]. Finally, a recent study confirmed the photoprotective and antiphotoaging effects of a nutritional intervention with different antioxidants, including LUT (3 mg/day), in healthy volunteers [193].…”
Section: Human Studiesmentioning
confidence: 99%